2016
DOI: 10.2217/cnc-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged cognitive–motor impairments in children and adolescents with a history of concussion

Abstract: Aim:We investigated whether children and adolescents with concussion history show cognitive–motor integration (CMI) deficits.Method:Asymptomatic children and adolescents with concussion history (n = 50; mean 12.84 years) and no history (n = 49; mean: 11.63 years) slid a cursor to targets using their finger on a dual-touch-screen laptop; target location and motor action were not aligned in the CMI task.Results:Children and adolescents with concussion history showed prolonged CMI deficits, in that their performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 66 publications
9
50
2
Order By: Relevance
“…The present findings combined with previous discoveries [8] may partially explain why youth who returned to game-play after a concussion are at a higher risk of incurring another concussion or injury within the first year post-injury [11,12]. In previous studies, it was shown that lingering eye-hand decoupling deficits remained present for much longer than previously expected in both asymptomatic youth [8,9] and asymptomatic elite athletes [14] who had all returned to play. In the present study, we expand on these findings with details about the time course of EHD deficits in youth with concussion history to include task demand.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The present findings combined with previous discoveries [8] may partially explain why youth who returned to game-play after a concussion are at a higher risk of incurring another concussion or injury within the first year post-injury [11,12]. In previous studies, it was shown that lingering eye-hand decoupling deficits remained present for much longer than previously expected in both asymptomatic youth [8,9] and asymptomatic elite athletes [14] who had all returned to play. In the present study, we expand on these findings with details about the time course of EHD deficits in youth with concussion history to include task demand.…”
Section: Discussionsupporting
confidence: 77%
“…In line with these findings, previous work has shown prolonged eye-hand coordination deficits in youth with concussion history for up to 1.5 years post-concussion when participant's performed a challenging cognitive-motor task that required a decoupling of eye and hand movement direction [8,9]. Importantly, all of the young athletes involved in these studies had already returned to game play after their concussion, in accordance with the current return to play protocols at the time the concussion-incident occurred [10].…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations